A CROSS-SECTIONAL STUDY OF MEDICAL PRACTITIONERS’ KNOWLEDGE AND ATTITUDES ON HYPERBARIC OXYGEN THERAPY FOR CHRONIC WOUNDS IN KELANTAN, MALAYSIA - Idris, Iqlima; Mafauzy, Mohamad Masykurin; Nik Ab Rahman, Nik Hisamuddin; Md Noh, Abu Yazid; Wan Mohamad, Wan Syahmi; Mohamad, Ahmad Rasyidi (Malaysian Journal of Public Health Medicine, 2026)
This study assesses the knowledge and attitude of medical practitioners toward hyperbaric oxygen therapy (HBOT) in the treatment of chronic wounds. HBOT has been increasingly recognised as an adjunctive treatment for chronic, non-healing wounds, yet its adoption in clinical practice remains limited. A cross-sectional study was conducted involving 197 medical practitioners from various clinical departments in a tertiary hospital. A validated self-administered questionnaire was used to assess their knowledge and attitude toward HBOT. Descriptive statistics were used to summarise the data, and logistic regression analyses were performed to identify significant predictors. The results showed that 70.6% of respondents demonstrated good knowledge of HBOT, while 65.0% exhibited a positive attitude toward its use in chronic wound management. The only significant predictor of good knowledge was the duration of medical practice. A positive attitude was strongly associated with three things: seeing a higher volume of wound care patients each month, having prior experience referring patients for HBOT, and having more years in practice. Additionally, practitioners with good knowledge were 6.62 times more likely to have a positive attitude toward HBOT. Although most practitioners were knowledgeable and supportive, gaps remain in practical experience, particularly regarding cost-effectiveness and accessibility. These findings underscore the need for structured continuing medical education, postgraduate training, and clearer referral pathways to enhance the integration of HBOT into chronic wound management.